Penguatan Kedisiplinan Keuangan Melalui Edukasi Uang Saku Pada Siswa SD Negri 35 Oku di Desa Air Jati Batumarta II - Anggini, Marcha Dwi; Mutia, Rizqi Alifa; Putra, Fondra Pama; Pildi, Eleta; Sari, Enda Kartika (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This activity aims to educate primary school children to understand money properly, manage their pocket money wisely, and understand the importance of saving for the future. The activity was carried out in Air Jati Village, Batumarta II Subdistrict, targeting students in grades III to VI of SD Negeri 35 OKU. The method used was socialisation through direct delivery of material, accompanied by the provision of piggy banks as a means of supporting the habit of saving. The results of the activity showed that before the education, most children had a low level of understanding of pocket money management. Children generally viewed money only as a means to buy snacks or toys, did not have active savings, and were not accustomed to managing their pocket money in a planned manner. After the activity was carried out, the participants showed an increase in their understanding of the function of money, the importance of saving, and simple ways to manage pocket money. All participants enthusiastically participated in the activity and were actively involved in each stage carried out by the community service team. This activity is expected to be the first step in instilling financial literacy from an early age.